Category of Tonality Explicated in the Texts of Virtual Genre - Natalia А. Ryadovykh (Виртуальная коммуникация и социальные сети)
The research dealt with the category of tonality explicated in the texts of virtual communication. It featured the official community of students, graduates, academics, and employees of the Ural State Law University in the Vkontakte social network. The research objective was to identify the specifics of tonality in the communicative and pragmatic aspects of the virtual genre. The method of categorical-textual analysis revealed the types of tonality that made up the tonal field of virtual communication, as well as their linguistic explication means at the lexical, morphological, syntactic, and graphical levels. A specific transformation of tonal varieties proved to be a characteristic feature of the hybrid virtual genre: it combined a monologue text and a reflective commentary on it. The neutral and benevolent tonalities of the monologue tonal core were complemented by peripheral varieties of the commentary text with pleading and disapproving tonalities. In the commentary texts, the tonality of benevolence remained in the core, while the neutral tonality became peripheral. The communicative and pragmatic solution was evaluated as positive when the tonality in the tonal core of monologue texts and comments was benevolent, or when the neutral tonality of the monologue text turned benevolent in the commentary. These tactics yielded a positive perception of the information presented by the sender of the message.